On the Properties of Shuffle Dislocation in BC5: Core Structure and Peierls Barrier and Stress - Zhang, H.L.; Wu, X.H.; Yuan, C.J. (Asian Journal of Chemistry, 2014)
The dislocation widths for shuffle 60º and screw dislocations in diamond like BC5 have been calculated by the improved Peierls-Nabarro theory in which the discrete effect has been taken into account. For the dislocations with same angles, the width of dislocation located between B-C layers is about 1.2 times wider than that located between C-C layers. For the dislocations located between same layers, the width of 60º dislocation is about 1.4 times wider than that of the screw dislocation. Peierls barriers and stresses have been evaluated with considering the contribution from both misfit and strain energies. The Peierls barriers for shuffle 60º and screw dislocations in BC5 are, respectively about 0.059 and 0.167 eV/Å, Peierls stresses are, respectively about 5 and 15 GPa. The results calculated in this paper are useful for data analysis of experiments.